Participatory and Inclusive Environment Improves Student Academic Achievement - Waruwu, Ermina; Sitanggang, Nathanael; Sinaga, Osberth (Universitas Pendidikan Ganesha, 2024)
Good management that can integrate the concepts of participation and inclusion into educational institutions' policies, practices, and culture is sometimes not optimal. Based on this, this research aims to analyze the influence of a participatory and inclusive environment on student academic achievement. This research uses a type of comparative causal research with a quantitative approach. The population in this study was 222 students. The sampling technique is a probability sampling technique with simple random sampling. The number of samples in this research was 38 students. The methods used to collect data are questionnaires and documentation. The instrument used in this research was a questionnaire sheet. The technique used to analyze data is regression analysis. The research results show that a participatory and inclusive environment fosters a learning atmosphere that fosters high student participation. Facilities, accessibility, academic support, and free speech contribute to understanding and growth. Academic achievement, as assessed through grades, recognition, pass percentage, understanding of standardized tests, and involvement in extracurricular activities, is positively influenced. Lecturer evaluations are considered useful, and statistically, participatory and inclusive environments positively impact academic performance. Recommendations for further research include increasing student involvement, improving facilities, and strengthening academic support and student welfare. The implication of this research is that a participatory and inclusive environment that is implemented optimally will have an impact on increasing student academic achievement.